Pengaruh Variasi Tekanan Pada Hydrostatic Test Terhadap Pengelasan Gas Tungsten Arc Welding (GTAW) Pipa Baja ASTM A106 - Rohadin Rohadin; Kardiman Kardiman; Deri Teguh Santoso (Jurnal Ilmiah Wahana Pendidikan, 2023)
Pipes are tools for flowing fluids. In the mining sector, energy makes a major contribution to the use of pipes. ASTM A106 steel is a low carbon steel pipe used for high temperature applications (up to 750 degrees F). This pipe is able to withstand high temperatures and high pressures, so it is widely used in the oil and gas, petrochemical, power generation, and ship building industries. The purpose of this study was to determine the effect of variations in the pressure of the Hydrostatic test on ASTM A106 steel pipe welding joints with a current of 90 A and variations in the pressure of the Hydrostatic test of 450 Psi, 1150 Psi and 2225 Psi. The results showed that there were imperfect melting defects, excessive root penetration, porosity, and root concavity. For the Hydrostatic test with pressure variations of 450 Psi, 1150 Psi and 2250 psi for 3 pipes, the results showed that there were no leaks in the three pipes. 405.33 and the lowest uji tarik is found in spesimens that have been subjected to a Hydrostatic test with a pressure of 450 Psi with a uji tarik of only 367.01 .